VALIDATION OF A TOOL TO MEASURE THE LEVEL OF SCHOOL-UNIVERSITY PARTNERSHIP - Hong, Cao Thuy; Anh, Tran Thi Lan (VNU Journal of Foreign Studies, 2022)
This study aims at developing and validating an audit tool that could be used to assess school-university partnerships. Specifically, the study followed four steps of (i) evaluating and modifying contents and items of the original tool, (ii) qualitatively assessing content validity of the revised scale basing on expert ratings, and revising the scale accordingly, (iii) conducting cognitive interviews with potential participants, and making further revision, and (iv) quantitatively evaluating the validity and reliability of the audit tool based on data collected from 463 participants, and finalizing the tool. In the end, an audit tool consisting of 36 questions that fit into two scales (i.e., “Shared goals and values”  and “Partnership operations and management” ) was confirmed. The study also discussed potential uses of the tool for both currently working partnerships  and newly formed partnerships ; and at different levels .